Konsep Fitnah Dalam Al Qur'an Surah Al Baqarah Ayat 191 dan 217: Studi Komparatif Tafsîr Al-Kasysyâf Karya Az-Zamakhsyarî dan Mafâtîh Al-Ghaib Karya Fakhruddîn Ar-Râzî - iskandar, iskandar; Mursalim, Mursalim; Fansuri, Fuad; Muhammad Salam, Mukhtar (Tasamuh: Jurnal Studi Islam, 2023)
In general society, the word slander is not a new language. However, the interpretation of the word slander that has existed among the public is often limited to what is meant by accusing it with bad allegations and then following it with evidence in the form of fragments of verses from the QS. Al-Baqarah verse 191 or 217 so it may not lead to the intended purpose of these two verses. The author uses data sourced from journals, commentary books and several literature related to research. Because it focuses on both classical and modern literature, this research is qualitative or library research (literature research) by utilizing comparative methods (muqarran) to compare the interpretations of the two. After conducting research, it can be seen that the comparison of the words slander according to Az-Zamakhsyari and Fakhr ad-Din ar-Razi is concluded with 5 meanings, slander means gold nuggets that are placed on fire to obtain the purity of the gold which then leads to severe trials or are called al-mihnah and al-bala', slander is an eternal punishment that binds a person because disbelief, the prohibition of entering the Grand Mosque and the apostasy of non-believers. The similarities include both methods, namely the tahlili method with the bi al-ra'yi interpretation style and interpreting slander with al-ikhraj. Meanwhile, the differences include the background of Az-Zamakhsyari's writing of al-syirku which is side by side with the interpretation of the root word "al-kufru" belonging to al-Razi.